The well-being costs of informal caregiving - Michael Krämer; Wiebke Bleidorn (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
How does informal care affect caregivers' well-being? Theories and existing research provide conflicting answers to this question, partly because the temporal processes and conditions under which different aspects of well-being are affected are unknown. Here, we used longitudinal data from Dutch, German, and Australian representative panels (281,884 observations, 28,663 caregivers) to examine theoretically derived hypotheses about changes in caregivers' life satisfaction, affective experiences, depression/anxiety, and loneliness. Overall, results provided evidence for negative well-being effects after the transition into a caregiver role, with more pronounced and longer-lasting well-being losses in women than men. We further found that well-being losses were larger with more time spent on caregiving, in both men and women. These results were robust across moderators of the caregiving context (care tasks, relationship with care recipient, and fulltime employment). Together, the present findings support predictions of stress theory and highlight lingering questions in theoretical frameworks of care-related well-being costs.
Keywords: 330; informal care; caregiving; well-being; life satisfaction; affect; mental health